Dialogic supervision: Investigating supervision practices of English pre-service teachers in a professional training program (PLP) - Amirulloh, R. Della Nuridah Kartika Sari; Lengkanawati, Nenden Sri; Setyarini, Sri (Universitas Pendidikan Indonesia, 2019)
This paper serves as a preliminary study of the dialogic supervision as a breakthrough to improve the performance of pre-service English teachers in a Program Latihan Profesi/Professional Training Program (PLP). In detail, this research is aimed at: (1) investigating the pattern of ongoing PLP supervising, (2) identifying if there is an indication of dialogical supervision and (3) identifying the difficulties the pre-service teachers faced during their supervision. The Research and Development was designed for three years. The subjects of this research are pre-service teachers, supervisory teacher and supervisory lecturer.Â The data were collected through three instruments, such as observation, interview with pre-service teachers, interview with both supervisory teachers and lecturers, and questionnaires distributed to the pre-service teachers. The first-year findings show that the current supervision pattern tends to be conventional as seen from several aspects: face-to-face technique, formal situation, instructional language, supervisory lecturer and the teacher still dominate in the supervision discussion, non-problem based supervision topic, and the low frequency of meetings. On the other hand, some points are identified within the pattern of dialogical supervision, i.e., collegial language, independent reflection, friendly, flexibility of time and place.Â Besides, there are some problems faced by the supervisory lecturers and teachers, among other time limitation, less contextual supervision material, poor coordination, ineffective feedback. Therefore, the solutions include supervision planning coordinated by all three parties and made into a schedule, optimum use of social media, supervision material selection is based on the needs of the pre-service teachers.